Antibacterial Potential Of Root And Bark Of Cocos Nucifera Linn. Against Isolated Urinary Tract Infection Causing Pathogens - M. KOMALA SIVAKUMAR,; M. MOHAMMED MOIDEEN,; RUBY VARGHESE,; K.P. SAMPATH KUMAR, (International Journal of Pharma and Bio Sciences, 2011)
The study was carried out to evaluate the antibacterial potential of Cocos nucifera Linn. root and bark against isolated UTI (urinary tract infection) causing pathogens. In the study, the following bacteria were used: E. coli, P. aeruginosa, S. aureus and K. pneumonia. Amikacin taken at 1mcg/disc was selected as the standard drug. Phytochemical tests were performed for the identification of various plant constituents. Other tests which were carried out were determination of ash values and antibiotic susceptibility tests. The study revealed that the root and bark of plant Cocos nucifera Linn. showed antibacterial activity against all the UTI isolates. The study concluded that the aqueous extract of root of Cocos nucifera Linn. was found to be more effective in inhibiting the growth of UTI pathogens than the ethanolic extract and decoction.